1990
DOI: 10.1148/radiology.176.3.2389026
|View full text |Cite
|
Sign up to set email alerts
|

Vascular metastatic lesions of the spine: preoperative embolization.

Abstract: Preoperative embolization of vascular metastatic tumors of the spine, particularly carcinomas of renal and thyroid origin, is an adjuvant technique that significantly decreases the intraoperative blood loss and resultant surgical morbidity. Surgical decompression was achieved in 24 spinal vascular metastatic lesions, 20 of which were treated with preoperative embolization and four of which were not. The embolic materials used were gelatin sponge, polyvinyl alcohol foams, and metallic coils. In patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 0 publications
1
70
2
Order By: Relevance
“…No agreement exists on the effect of degree of devascularization on estimated blood loss. Some authors suggest that tumor devascularization reduces estimated blood loss [2,4,6,16]; however, some have found no correlation between tumor devascularization and estimated blood loss [7]. In our study, we found no correlation between degree of devascularization and estimated blood loss.…”
Section: Discussioncontrasting
confidence: 93%
“…No agreement exists on the effect of degree of devascularization on estimated blood loss. Some authors suggest that tumor devascularization reduces estimated blood loss [2,4,6,16]; however, some have found no correlation between tumor devascularization and estimated blood loss [7]. In our study, we found no correlation between degree of devascularization and estimated blood loss.…”
Section: Discussioncontrasting
confidence: 93%
“…The most highly vascularized vertebrae are those with metastases originating from renal cell and thyroid carcinoma [7]. Life-threatening blood losses have been described in cases without preoperative embolization [3,6] Abstract The aim of this study was to evaluate the impact of preoperative devascularization of spinal metastases in relation to the preembolization tumor vascularization degree and in relation to the intraoperative blood loss. Twenty-four patients underwent preoperative transarterial embolization of hypervascular spinal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is recommended that embolisation should be performed as close as possible to the time of surgery. Typically, best results are achieved when surgery is performed within 24-48 h after embolisation [58,[61][62][63].…”
Section: Treatmentmentioning
confidence: 99%